Advancing immunosuppression in liver transplantation: the role of regulatory T cells in immune modulation and graft tolerance - Ji Won Han; Su-Hyung Park (Clinical Transplantation and Research)
Prolonged immunosuppressive therapy in liver transplantation (LT) is associated with significant adverse effects, such as nephrotoxicity, metabolic complications, and heightened risk of infection or malignancy. Regulatory T cells (Tregs) represent a promising target for inducing immune tolerance in LT, with the potential to reduce or eliminate the need for life-long immunosuppression. This review summarizes current knowledge on the roles of Tregs in LT, highlighting their mechanisms and the impact of various immunosuppressive agents on Treg stability and function. The liver’s distinct immunological microenvironment, characterized by tolerogenic antigen-presenting cells and high levels of interleukin (IL)-10 and transforming growth factor-β, positions this organ as an ideal setting for Treg-mediated tolerance. We discuss Treg dynamics in LT, their association with rejection risk, and their utility as biomarkers of transplant outcomes. Emerging strategies, including the use of low-dose calcineurin inhibitors with mammalian target of rapamycin inhibitors, adoptive Treg therapy, and low-dose IL-2, aim to enhance Treg function while providing sufficient immunosuppression. Thus, the future of LT involves precision medicine approaches that integrate Treg monitoring with tailored immunosuppressive protocols to optimize long-term outcomes for LT recipients.